Exploring Stigma in Low HIV Prevalence Settings in Rural West Bengal, India: Identification of Intervention Considerations. (October 2015) - Panda, Samiran; Das, Ranjan Sourav; Maruf, S. K. Abdullahil; Pahari, Sobha
This community-based concurrent mixed methods study identified specific cases of discrimination and explored HIV stigma. In-depth interviews were conducted with individuals experiencing discrimination, and a quantitative survey was conducted in the immediate neighborhood. Focus group discussions were held with opinion makers. Survey respondents not attending school and believing in mosquito-borne HIV transmission had twice the odds of having fear of contracting HIV through noninvasive contact. In contrast, correct knowledge of mother-to-child HIV transmission was associated with judgmental attitudes, and knowledge of the role of condoms in HIV prevention was associated with shame. Qualitative investigations corroborated these findings, documented the denial of rights of people living with HIV, and revealed that discrimination resulting from fear of contagion directed against women had a moral dimension. Thematic issues and communication strategies were identified and translated into an intervention development.